2004
DOI: 10.1111/j.1360-0443.2004.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

The adolescent behavioral repertoire as a context for drug exposure: behavioral autarcesis at play

Abstract: The study evidence lends some support for behavioral autarcesis. Manipulation of selected ABR dimensions might help prevent or reduce adolescent drug involvement, enhancing autarcesis as a protective mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…However, only recently has delinquency been investigated in relation to early drug use opportunities and not necessarily drug use per se (Chen et al, 2004;Neumark et al, 2012;Rosenberg and Anthony, 2001). Our results reiterated the importance of such early problems, as delinquent youth emerged as the likely targets for cannabis offers.…”
Section: Cannabis Offerssupporting
confidence: 56%
“…However, only recently has delinquency been investigated in relation to early drug use opportunities and not necessarily drug use per se (Chen et al, 2004;Neumark et al, 2012;Rosenberg and Anthony, 2001). Our results reiterated the importance of such early problems, as delinquent youth emerged as the likely targets for cannabis offers.…”
Section: Cannabis Offerssupporting
confidence: 56%
“…Past research among Central American adolescents from the PACARDO Project has shown that among adolescents aged 12-20 years who were attending school, over half (51.5%) had tried alcohol, 29.1% had tried tobacco, and 4.6% had tried marijuana [1]. (The PACARDO name concatenates PA for Panamá, CA for Centroamérica, and RDO for República Dominicana.…”
mentioning
confidence: 99%
“…Protective factors include being married (Judd et al, 2002;Teesson, Dietrich, Degenhardt, Lynskey, and Beard, 2002), having children, and having religious involvement (Chen et al, 2004;Galen and Rogers, 2004), as well as higher education ( In this paper we examine prevalence of hazardous use of alcohol, tobacco, and other drugs among demographic subgroups, in a large, representative sample of patients using the primary care service of the public health system in Cape Town, South Africa. …”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, the racial categories defined under apartheid-Black, Colored (mixed race), Indian, and White-have a long association in South Africa with access both to alcohol and to treatment (Mager, 2004). Different race groups may demonstrate different prevalence or responses to risk factors by gender (Flisher, Parry, Evans, Muller, and Lombard, 2003).Young adults who use substances may be more at risk for other health risks such as sexual risk behaviors, violence, and suicide (Flisher, Ziervogel, Chalton, Leger, and Robertson, 1996).Protective factors include being married (Judd et al, 2002;Teesson, Dietrich, Degenhardt, Lynskey, and Beard, 2002), having children, and having religious involvement (Chen et al, 2004;Galen and Rogers, 2004), as well as higher education ( In this paper we examine prevalence of hazardous use of alcohol, tobacco, and other drugs among demographic subgroups, in a large, representative sample of patients using the primary care service of the public health system in Cape Town, South Africa. …”
mentioning
confidence: 99%
See 1 more Smart Citation